2019
DOI: 10.1093/rb/rbz035
|View full text |Cite
|
Sign up to set email alerts
|

Integrated prodrug micelles with two-photon bioimaging and pH-triggered drug delivery for cancer theranostics

Abstract: Nanodrug carriers with fluorescence radiation are widely used in cancer diagnosis and therapy due to their real-time imaging, less side effect, better drug utilization as well as the good bioimaging ability. However, traditional nanocarriers still suffer from unexpectable drug leakage, unsatisfactory tumor-targeted drug delivery and shallow imaging depth, which limit their further application in cancer theranostics. In this study, an integrated nanoplatform is constructed by polymeric prodrug micelles with two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…ROP is executed typically in the presence of metal carboxylate with a hydroxyl-containing compound, normally alcohols, H 2 O, or macromolecules with hydroxy end group (denoted as ROH). Poly(ethylene glycol) (PEG) is one of the most common hydroxyl-containing chemicals in assisting synthesis of polyesters, and PEG itself is a hydrophilic polymer which has been widely applied as medical excipient and bio-matrix [ 49 , 50 , 51 ].…”
Section: Synthesis Of Plamentioning
confidence: 99%
“…ROP is executed typically in the presence of metal carboxylate with a hydroxyl-containing compound, normally alcohols, H 2 O, or macromolecules with hydroxy end group (denoted as ROH). Poly(ethylene glycol) (PEG) is one of the most common hydroxyl-containing chemicals in assisting synthesis of polyesters, and PEG itself is a hydrophilic polymer which has been widely applied as medical excipient and bio-matrix [ 49 , 50 , 51 ].…”
Section: Synthesis Of Plamentioning
confidence: 99%
“…64 The pH-responsive AIEgen platform (such as drug molecules grafted pH-responsive polymer with AIE characteristics 65,66 ) induces fluorescence imaging capabilities and deliver therapeutic molecules to eliminate tumor upon a trigger by the acidic tumor environment. 67,68 Such pH-responsive AIE theranostic system specifically light up the tumor and deliver drug molecule avoiding damage to the surrounding normal cells. 69 Owing to the needs in the biological application, the characteristics of AIEgens are integrated for multifunction biomedical applications, such as imaging and image-guided theranostic applications.…”
Section: Applications Of Aiegensmentioning
confidence: 99%
“…After cellular uptake, the elevated intracellular ROS can disrupt the boronic ester bond and trigger the release of Cap for effective tumor therapy. In a subsequent study, they have also reported another prodrug micellar system with a neutral hydrophilic pH-detachable PEG shell and a dimethylmaleic anhydride-grafted-polyethyleneimine segment charge reversable segment [ 71 ]. While the AIE two-photon probe was chemically conjugated to the hydrophobic chain end, the therapeutic drug DOX was conjugated to the main backbone via an acid-labile imine bond.…”
Section: Polymeric Nanoplatforms For Two-photon-assisted Theranostic ...mentioning
confidence: 99%